Neuroprotective effect of mesenchymal stem cell through complement component 3 downregulation after transient focal cerebral ischemia in mice. (28th October 2016) - Jung, Hye-Seon; Jeong, Si-Yeon; Yang, Jiwon; Kim, So-Dam; Zhang, Baojin; Yoo, Hyun Seung; Song, Sun U.; Jeon, Myung-Shin; Song, Yun Seon
Highlights: MSCs reduced cerebral ischemic damage as well as complement component 3 levels in a mouse model of transient focal cerebral ischemia. Inflammatory factors such as IL-6, CCL2, TSG-6 and IL-17A were modulated by administration of MSCs in brain and blood of mice. Inhibition of complement component 3 was confirmed by MSCs treatment in oxygen glucose deprivation of primary neuron culture. Abstract: Bone marrow-derived mesenchymal stem cells (MSCs) are used in stroke treatment despite the poor understanding of its mode of action. The immune suppressive and anti-inflammatory properties of MSCs possibly play important roles in regulating neuroinflammation after stroke. We investigated whether MSCs reduce the inflammatory complement component 3 (C3) levels, thus, providing neuroprotection during stroke. Mice were subjected to transient focal cerebral ischemia (tFCI), after which MSCs were intravenously injected. The infarct volume of the brain was reduced in MSC-injected tFCI mice, and C3 expression was significantly reduced in both the brain and the blood. Additionally, the profiles of other inflammatory mediators demonstrated neuroprotective changes in the MSCs-treated group. In order to analyze the effect of MSCs on neurons during cerebral ischemia, primary cortical neurons were co-cultured with MSCs under oxygen-glucose deprivation (OGD). Primary neurons co-cultured with MSCs exhibited reduced levels of C3 expression and increased protection against OGD, indicating that treatment with MSCs reduces excessive C3 expression and rescues ischemia-induced neuronal damage. Our finding suggests that reduction of C3 expression by MSCs can help to ameliorate ischemic brain damage, offering a new neuroprotective strategy in stroke therapy.